2019
DOI: 10.24323/akademik-gida.667270
|View full text |Cite
|
Sign up to set email alerts
|

Fenolik Bileşiklerin Bağlı Formları ve Biyoyararlılığı

Abstract: O. Yemiş) 0 264 295 31 92 0 264 295 56 01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 91 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The phenolic compounds performance play an important role in retaining the balance between oxidants and antioxidants in the body. Studies have shown that dietary intake of phenolic compounds associated with oxidative stress can prevent diseases such as cancer, high cholesterol, coronary heart, cataracts, diabetes, cardiovascular diseases, and aging (Karabulut & Yemiş, 2019). Total phenolic and flavonoid contents of G. biloba leaf methanol extract were measured as 71.20±0.42 µg GAE/mg extract and 13.24±0.35 µg QE/mg extract, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds performance play an important role in retaining the balance between oxidants and antioxidants in the body. Studies have shown that dietary intake of phenolic compounds associated with oxidative stress can prevent diseases such as cancer, high cholesterol, coronary heart, cataracts, diabetes, cardiovascular diseases, and aging (Karabulut & Yemiş, 2019). Total phenolic and flavonoid contents of G. biloba leaf methanol extract were measured as 71.20±0.42 µg GAE/mg extract and 13.24±0.35 µg QE/mg extract, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that sprouts have more antioxidant content than seeds. In another study, it was mentioned that kumestrol, obtained from soybean sprouts, suppresses prostate cancer (Karabulut and Yemiş, 2019;Kalaycı and Kaya, 2022) High blood pressure or hypertension, which is a symptom of cardiovascular diseases, is one of the important causes of death. High blood pressure can be controlled through diet.…”
Section: Effects Of Seed Sprouts On Human Healthmentioning
confidence: 99%
“…Phenolic compounds show antioxidant activity in the body due to their free radical capture capacity and are associated with many diseases [ 121 ]. They also prevent oxidative DNA damage by inhibiting the binding of carcinogens to DNA.…”
Section: Phenolic Compoundsmentioning
confidence: 99%